Evaluation of pharmacy-led weight management service to minimise the risk of cardiovascular disease - Aliki Peletidi; Reem Kayyali (Taylor & Francis Group, 2021)
Aims The primary aim of the programme was a minimum of a 5% weight reduction of the initial weight, while the secondary outcomes were a reduction in participants' body mass index (BMI), waist circumference (WC), blood pressure (BP), AUDIT-C score and an increase in the Mediterranean diet (MD) score and an improvement in physical activity levels. Methods This 'before and after' study was a 10-week weight management (WM) programme and it was developed and delivered in community pharmacies in Patras chosen for convenience, thus consisting the first service of its type in Greece. The sample size was calculated (n = 96) based on the mean BMI for a Greek male and female individual, and the standard deviation (SD) of weight at baseline of 14 kg. Results Nearly every participant enrolled in the 20 participating pharmacies, 97.4% (n = 114/117), achieved the programme's aim, losing at least 5% of their initial weight. The mean percentage of total weight loss of the 117 participants at the 10th week was 8.97% (SD 2.65), and the t-test showed statistically significant results (P-value < 0.001; 95% CI [8.48, 9.45]). A significant reduction in the waist-to-height ratio (WHtR) was observed in both male (P-value = 0.004) and female (P-value < 0.001) participants. The participants' BP and AUDIT-C score and physical activity levels significantly improved (P-value < 0.001), as well as their MD score. Conclusion This study provides the first evidence that Greek pharmacists have the potential to play an important role within primary healthcare and that after training they are able to provide public health services for both the public's benefit and their clinical role enhancement.